IMR 665: Management of Audio Visual Records & Archives. Individual assignment: Article summary / Sumiyyah Kamaruzaman - Kamaruzaman, Sumiyyah (2015)
Article on: Article 1 - “A research of audio visual educational aids on the creativity levels of 4-14 year old children as a process in primary education” Article 2 - “Investigating the effect of audio visual materials as warm-up activity in Aviation English courses on students’ motivation and participation at high school level”